Divided Consciousness in The Bluest Eye - Shrestha, Ravi Kumar (Cognition, 2022)
Toni Morrison’s novel The Bluest Eye uncovers the identity conflicts between the African- Americans and the whites due to the notions of Eurocentrism, America-centrism, racism, and dominance of the west over the east. This paper explores an African-American girl Pecola’s divided identity because of the reasons such as Dominance of West over the East, Being Black Immigrant, Lack of Recognition from Home and Society, Racism, and Poverty and Lack of Social security. The tragic part of their getting victimized is that due to the white standard of beauty even blacks regard themselves ugly and inferior, which gets analyzed by the use of W. E. B. Du Bois’ theory of double consciousness. Though the novel shows both reasons and consequences of an African-American girl Pecola’s divided identity, my paper mainly focuses on the reasons for Pecola’s divided identity.